تأثير نظم التسميد في مساحة المسطح الورقي وصفات التبكير لنبات القطن - عبد العزيز, محمد علي; جراد, سمير علي; علي, بسام نهيت (Latakia University Journal -Biological Sciences Series, 2013)
نفذ البحث خلال الموسميين الزراعيين 2009 – 2010 في محافظة الحسكة منطقة عامودا لدراسة تأثير السماد العضوي الغنمي بمعدل 30 طن/هـ وأربعة أنواع من السماد العضوي الأخضر (عدس، بيقية، فول، شعير) في مساحة المسطح الورقي وصفات التبكير لنبات القطن مقارنة مع السماد الكيميائي (400 كغ يوريا، 83 كغ P2O5، 25 كغ K2O/هـ). بينت الدراسة: تفوق التسميد بمخلفات الأغنام معنويا في زيادة (مساحة المسطح الورقي، وانخفاض توضع الفرع الثمري الأول، والتبكير في الأزهار، والتبكير في نضج الجوزات) عند مقارنته مع كافة الأنواع السمادية المدروسة وبزيادة وصلت إلى (190.92 سم2، و0.30 سلامية، و1.50 يوم، و0.90 يوم) على التوالي عند مقارنته مع السماد الكيميائي، وتفوقت الأسمدة الخضراء البقولية (عدس، بيقية، فول) معنويا في زيادة مساحة المسطح الورقي مقارنة مع الشاهد، وأثر السماد الأخضر البقولي (عدس) معنويا في التبكير في الأزهار (2.73) يوم ونضج الجوزات (2.21) يوم عند مقارنته مع السماد الأخضر النجيلي (شعير) ولم يؤثر السماد الكيميائي معنويا في التبكير في الأزهار ونضج الجوزات مقارنة مع السماد الأخضر (عدس). The research was carried out during 2009 – 2010 in Al – Hasaka – Amoda – to study the effect of cattle manure at the rate of 30 ton/h1, and four organic green fertilizers (Lentil, Vetch, Faba bean and Barely) on plant area and earliness properties of cotton crop compared with chemical fertilizer 400 kg/h1 urea, 83 kg/h1 P2O5 and 25 kg/h1 K2O.The study showed that the cattle manure significantly increased (plant area, lower first fruiting branch, earliness of flowering and boll maturity) when compared with all studied fertilizers, the increase reached (190. 92 Cm2, 0.30 pod, 1.50 day and 0.90 day) respectively. When compared with chemical fertilizer, the legume green fertilizers (Lentil, Vetch and Faba bean) significantly increased the plant area when compared with the control. The legume green fertilizer (Lentil) significantly increased the earliness of flowering (2.73) day and boll maturity (2.21) day when compared with the green fertilizer (Barely). The chemical fertilizer did not significantly affect the earliness of flowering and boll maturity when compared with the legume green fertilizer (Lentil) during the two seasons.